2016
DOI: 10.1002/srin.201500441
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Heating Experiments on BOF-Slag: Simultaneous Phosphorus Re-Distribution and Volume Stabilization for Recycling

Abstract: Basic-oxygen furnace (BOF) slag is the second abundant by-product from the steel-making process. It is not readily recycled for high phosphorus content and volume instability. To eliminate its phosphorus-hosting dicalcium silicate (C 2 S) and volumetrically unstable free-lime, reductive heating experiments on BOF-slag are carried out at 1300-1600 8C using quartz-sand or serpentine as a basicity modifier. In the products, C 2 S and free-lime are consumed through reacting with CaO and MgO, which are produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Accelerated carbonation treatment of slag has been demonstrated as an efficient way to eliminate the free lime by reacting with CO2 [11][12][13]. Basicity modifier such as SiO2 was examined as an effective agent by transforming the free lime and diacalcium silicate to merwinite and akermanite [14,15]. Recently, the present authors reported a novel lime stabilization method by cooling the slag in air, where wustite in the slag is oxidized to hematite and then stabilizes the free lime by forming calcium aluminoferrite [16].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated carbonation treatment of slag has been demonstrated as an efficient way to eliminate the free lime by reacting with CO2 [11][12][13]. Basicity modifier such as SiO2 was examined as an effective agent by transforming the free lime and diacalcium silicate to merwinite and akermanite [14,15]. Recently, the present authors reported a novel lime stabilization method by cooling the slag in air, where wustite in the slag is oxidized to hematite and then stabilizes the free lime by forming calcium aluminoferrite [16].…”
Section: Introductionmentioning
confidence: 99%